Correlations between structure and microwave dielectric properties of Co doped MgMoO4 ceramics. Issue 14 (1st October 2020) - Bian, Wenjie; Lu, Xiaochi; Wang, Yan; Zhu, Haikui; Chen, Tao; Ta, Shiwo; Zhang, Qitu
Abstract: Mg1- x Co x MoO4 ( x = 0.01–0.15) ceramics were prepared by traditional solid-state methods. The phase composition, crystalline structure, micromorphology, and microwave dielectric properties of Mg1- x Co x MoO4 ceramics were comprehensively studied. Mg1- x Co x MoO4 ceramics present monoclinic wolframite structures from x = 0.01 to x = 0.15 with Co occupying the Mg-site. With the addition of Co 2+, ε r of Mg1- x Co x MoO4 ceramics increase. Q × f is maximal at 5 mol% Co 2+ content. The Mg0.95 Co0.05 MoO4 ceramic exhibits an optimal microwave dielectric property: ε r = 7, Q × f = 59247 GHz, τ f = −68 ppm/°C. The Q × f values increase by 20% compared with the pure MgMoO4 ceramics ( 49149 GHz). Doping Co 2+ effectively promotes the densification of ceramics and increases ε r and Q × f . However, when the Co content exceeds 5 mol%, the decreased packing fraction and disorder distribution of ions contribute to the increase in dielectric losses. The correlations between Co 2+ substitution and wolframite structure have been discussed by Raman spectroscopy, FT-IR spectroscopy and Rietveld refinement.